3y(5y+9)=0

Simple and best practice solution for 3y(5y+9)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y(5y+9)=0 equation:


Simplifying
3y(5y + 9) = 0

Reorder the terms:
3y(9 + 5y) = 0
(9 * 3y + 5y * 3y) = 0
(27y + 15y2) = 0

Solving
27y + 15y2 = 0

Solving for variable 'y'.

Factor out the Greatest Common Factor (GCF), '3y'.
3y(9 + 5y) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'y' equal to zero and attempt to solve: Simplifying y = 0 Solving y = 0 Move all terms containing y to the left, all other terms to the right. Simplifying y = 0

Subproblem 2

Set the factor '(9 + 5y)' equal to zero and attempt to solve: Simplifying 9 + 5y = 0 Solving 9 + 5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 5y = 0 + -9 5y = 0 + -9 Combine like terms: 0 + -9 = -9 5y = -9 Divide each side by '5'. y = -1.8 Simplifying y = -1.8

Solution

y = {0, -1.8}

See similar equations:

| 63-6x=9+18 | | 5x-3(x-10)=100-2(3x+5) | | 2(g+6)=24 | | .83=-.4b+.33b | | 5(g+6)=24 | | 3(x^2+4x+4)=0 | | n+8m=d | | 30n=-5 | | x=42*7 | | 2x(x-1)=5(x+3) | | 2x^3-11x^2+22x-15=0 | | 5x+31=14x-92 | | 945000+x=10x | | X^3-2x^2+3x+4=0 | | 5x-3(x-2)=30-3(x+3) | | 0.2x^2-80x+2500=0 | | 2t=34 | | 19x-17=3(4x-13) | | E+5=25 | | 6x-11y=0 | | 0=(12x^2)+6x-18 | | 7x+2y=-15 | | t-11+3= | | 24d+12x+8d-12x= | | 10x-3y=43 | | x+7y=-36 | | 2x=b+1-ax | | x-7y=34 | | 6x+6-2x=0 | | 6-7a-5a^2=0 | | 8-(1-2m)=8+2(4m-3) | | 3x^4+4x^2+28x+5=0 |

Equations solver categories